INDIGENOUS SCHOOL EDUCATION: INTERCULTURAL, BILINGUAL, SPECIFIC, AND DIFFERENTIATED IN THE CONTEXT OF PUBLIC POLICIES IN ITACOATIARA – AM (REMUNOM, 2025)
This research aimed to analyze Indigenous school education in Itacoatiara, focusing on its legalprecepts and its relationship with public policies regarding the provision and implementation of thiseducational modality. It sought to answer the following questions: How are the principles ofintercultural, bilingual, specific, and differentiated Indigenous school education presented within thecontext of the municipality’s educational policies? What discourses emerge in the relationshipbetween what is legally established and what is actually implemented? The study also aimed tounderstand whether the policies developed by SEMED/Itacoatiara recognize the need for specific,differentiated, and quality Indigenous education, and whether there are practical conflicts andcontradictions to be overcome. The research followed a qualitative approach, using semi-structuredinterviews with coordinators and pedagogues from SEMED, as well as teachers working in schoolslocated in Indigenous territories in the Rio Urubu communities. The interviews were conducted viavideo calls due to challenges encountered during the data collection period. The scientific initiationproject titled “Intercultural, Bilingual, Specific, and Differentiated Indigenous School Education in theContext of Public Policies in Itacoatiara-AM” primarily aimed to identify the existing challenges topromoting quality Indigenous education, respecting the cultural and linguistic specificities of thesecommunities. The data revealed normative advancements, but also significant gaps between legalguidelines and the realities experienced by the communities. This research contributes to the debateon the implementation of equitable Indigenous school education, emphasizing ethnic diversity andensuring the rights of Indigenous peoples.